2002
DOI: 10.1046/j.1440-1827.2002.01417.x
|View full text |Cite
|
Sign up to set email alerts
|

Malignant phyllodes tumor of the prostate: Retrospective review of specimens obtained by sequential transurethral resection

Abstract: A case of malignant phyllodes tumor of the prostate in a 67-year-old man is reported. The patient was referred to a hospital for urinary retention. From material taken at three transurethral resections of the prostate (TURP), a histological diagnosis of benign prostatic hyperplasia was made. However, at the fourth TURP, phyllodes tumor was diagnosed due to the presence of elongated epithelial ducts and proliferating cellular stroma with mitosis and nuclear atypia. Two months later, total cystoprostatectomy was… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
32
0

Year Published

2004
2004
2020
2020

Publication Types

Select...
3
2
2

Relationship

0
7

Authors

Journals

citations
Cited by 28 publications
(33 citation statements)
references
References 18 publications
(39 reference statements)
1
32
0
Order By: Relevance
“…Previous studies 1,4 showed that prostatic STUMP typically express progesterone receptors/CD34, and focally express or do not express desmin. Although CD34 was considered as a useful marker of prostatic STUMP and PSS, there have been some reports 7,9 which demonstrated prostatic STUMP with negative immunohistochemical staining for CD34, similar with the findings in our patient. It should be noted that the results of immunohistochemical staining in stromal tumor of the prostate are ancillary and the most important criteria for diagnosis is the morphology by routine Hematoxylin and Eosin stain, as Hansel et al 10 emphasized.…”
Section: Discussionsupporting
confidence: 90%
See 2 more Smart Citations
“…Previous studies 1,4 showed that prostatic STUMP typically express progesterone receptors/CD34, and focally express or do not express desmin. Although CD34 was considered as a useful marker of prostatic STUMP and PSS, there have been some reports 7,9 which demonstrated prostatic STUMP with negative immunohistochemical staining for CD34, similar with the findings in our patient. It should be noted that the results of immunohistochemical staining in stromal tumor of the prostate are ancillary and the most important criteria for diagnosis is the morphology by routine Hematoxylin and Eosin stain, as Hansel et al 10 emphasized.…”
Section: Discussionsupporting
confidence: 90%
“…Some cases showed invasion to contiguous organs. In a minority of the cases, prostatic STUMP metastasizes to the lung and bone, and transforms to malignant PSS 1,[3][4][5][6][7] . Intriguingly, by Gaudin's classification, whereas the previous cases are mostly phyllodes tumor in type, the current case is pattern two of prostatic STUMP which spreads to right seminal vesicle and both lungs.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Unquestionably, the potential for sarcomatous transformation, recurrence, and infiltrative growth exists, but the frequency of these changes and their prognostic significance is unclear. [3][4][5][6][7] Little is known about the genetic abnormalities in this tumor. Oncogene activation and tumor suppressor gene inactivation are important mechanisms in the genesis, propagation, and spread of most cancers, but the role of these processes in phyllodes tumor has not been previously explored.…”
mentioning
confidence: 99%
“…Correct markers for gliomas are present, including invasive cell growth into the skin layer, necrotic areas with pseudopalisading, and poorly formed blood vessels [142].…”
Section: Discussionmentioning
confidence: 99%